THE RELATIONS BETWEEN INTERNATIONAL CPO PRICES AND DOMESTIC PALM OIL PRICES: A CAUSALITY APPROACH - Antik Suprihanti (Economic Journal of Emerging Markets, 2008)
The objective of this research is to analyze the trend of the Crude Palm Oil (CPO) prices in international Market at Rotterdam–Holland for the next two (2) years and to analyze the relations between international CPO prices and domestic palm oil prices in Indonesia.. The researcher uses linier trend method to analyze the trend and Granger causality approach. The results of the research show that the trend of international CPO prices tends to increase in 2008 and 2009. The causality analysis shows that international CPO prices causes domestic palm oil prices in Indonesia, but it is not vice versa. The result also shows that there is a positive relations between these prices. The increasing international CPO prices causes the rising of domestic palm oil prices. Keywords:    Crude Palm Oil (CPO), palm oil, international prices trend, domestic prices, causality approach.